The interplay between mitochondria, the gut microbiome and metabolites and their therapeutic potential in primary mitochondrial disease - Zachos, Kassandra A.; Gamboa, Jann Aldrin; Dewji, Aleena S.; Lee, Jocelyn; Brijbassi, Sonya; Andreazza, Ana C. (Frontiers in Pharmacology, 2024)
The various roles of the mitochondria and the microbiome in health and disease have been thoroughly investigated, though they are often examined independently and in the context of chronic disease. However, the mitochondria and microbiome are closely connected, namely through their evolution, maternal inheritance patterns, overlapping role in many diseases and their importance in the maintenance of human health. The concept known as the ‘mitochondria-microbiome crosstalk’ is the ongoing bidirectional crosstalk between these two entities and warrants further exploration and consideration, especially in the context of primary mitochondrial disease, where mitochondrial dysfunction can be detrimental for clinical manifestation of disease, and the role and composition of the microbiome is rarely investigated. A potential mechanism underlying this crosstalk is the role of metabolites from both the mitochondria and the microbiome. During digestion, gut microbes modulate compounds found in food, which can produce metabolites with various bioactive effects. Similarly, mitochondrial metabolites are produced from substrates that undergo biochemical processes during cellular respiration. This review aims to provide an overview of current literature examining the mitochondria-microbiome crosstalk, the role of commonly studied metabolites serve in signaling and mediating these biochemical pathways, and the impact diet has on both the mitochondria and the microbiome. As a final point, this review highlights the up-to-date implications of the mitochondria – microbiome crosstalk in mitochondrial disease and its potential as a therapeutic tool or target.